Influence of adolescents’ tendency to catastrophise on non-suicidal self-injury behaviour: A moderated mediation model - Lan, Zhensong; Pau, Kee; Yusof, Hapsah Md; Zhao, Qi; Liang, Fangmei; Huang, Xuefang (Frontiers in Psychology, 2022)
Adolescence is the peak period of non-suicidal self-injury (NSSI) behaviour, and it is also a period when the prevention and intervention in NSSI are frequently required. To explore the relationship between catastrophising and NSSI and its mechanism, the mediating effects of parental support and negative emotions on catastrophising and NSSI were analysed. A questionnaire was administered to 401 middle school students with a history of NSSI behaviour from 12 schools in Guangxi. (1) Adolescents’ catastrophising tendencies positively predicted their NSSI status through negative emotions（B=0.274, P＜0.001). The more severe the adolescents' catastrophising tendency, the more likely they were to have stronger negative emotions and thus show an increased NSSI level. (2) Parental support played a positive moderating role between the tendency to catastrophise and negative emotions (B = -0.101, t = -2.694, P < 0.01), and it had a protective effect on adolescents' NSSI. Catastrophising was less likely to induce the NSSI behaviour by reducing adolescents' negative emotions (B=-0. 104, t=-2. 313, P<0. 05); however, it should be noted that only parental affective support,informative support, and instrumental support played a significant mediating role. Parental support of adolescents has positive effects on the tendency to catastrophise, negative emotions, and NSSI, and it has some implications for the prevention and intervention of adolescents' NSSI.